Characteristics of Ultrasound and Magnetic Resonance Imaging of Normal Testes and Epididymis Besides Angiography of Testicular Artery in Dromedary Camel - Sary, Ramadan; Khalil, Karim; Sindi, Ramya A.; Mohamed, Ragab H.; Hussein, Hassan A.; Eid, Refaat A.; Samir, Haney; Alkahtani, Mohammed M.; Swelum, Ayman A.; Ahmed, Ahmed E. (Frontiers in Veterinary Science, 2022)
Decreasing male fertility encouraged the investigators to innovate accurate diagnostic non-invasive methods for detection of changes in the testicular parenchyma. Ultrasonography (US) has the potential to be used in this manner for decades, but magnetic resonance imaging (MRI) is still of limited application in animals for this purpose. The current study was designed to describe appearances and quantitative MRI attributes of the normal testes, epididymis besides angiography of testicular artery in camels. Thirty apparently healthy male dromedary camels aged 8 to 14 years were slaughtered during the rutting season. Immediately after slaughtering, the male gonads (n=30 pairs of testicles and epididymis) were subjected to morphometric evaluation using a vernier caliper and ultrasound scanning. Epididymial sperms were evaluated for motility, vitality and abnormality. MRI was performed for testes (n=16) by using a 1.5T Excite-II MRI apparatus of Sigma. Radiography and angioarchitecture of testicular artery (n=24) were done. Camel testicular length, width, and depth showed non-significant differences between a vernier caliper or sonar. The MRI results revealed that both the testis and epididymis have homogenously intermediate signal (T1) and testes have hyperintense signal, with slightly lower signal in the epididymis (T2). In conclusion, both the ultrasonography and MRI techniques, with each respective computer-assisted imaging, could be used to detect the histomorphological changes of the camels’ testicles. However, US imaging remains the first diagnostic technique for evaluating the reproductive health in males for its lower cost and accuracy. MRI is beneficial when the sonograms are inconclusive and/or equivocal. It shows the examined tissues in greater anatomical details compared to ultrasonography. Further studies are needed to compare between characteristics of US and MRI of normal testes and epididymis with testicular artery angiography in living camel during rut season and non-rut season and between normal healthy and affected diseased genitalia.